Pengaruh Budaya Organisasi Terhadap Pengembangan Karir yang di Mediasi oleh Self Efficacy pada Pegawai Kementerian Hukum dan HAM Kanwil Provinsi Gorontalo - Iyit Haris Moha; Robiyati Podungge; Rezkiawan Tantawi; Heldy Vanni Alam; Andi Yusniar Mendo (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This research aims to determine the influence of Organizational Culture on Development mediated by Self Efficacy (Study of Employees of the Gorontalo Ministry of Law and Human Rights Regional Office). The sampling technique uses nonprobability sampling with the technique taken, namely saturated sampling. The saturated sampling technique means that all members of the population are sampled, so that the sample used in this research is 121 employees. The data collection technique uses a questionnaire. The analytical test tool used to test this research is path analysis. The data analysis method uses the SPSS 27 application.. Based on the path analysis test, the results of this research show that organizational culture has a positive and significant effect on career development, organizational culture has a positive and significant effect on self-efficacy, self-efficacy has a positive and significant effect on career development, self-efficacy acts as a partial mediation between the relationship between organizational culture and employee career development. In this research, it is explained that the Career Development variable is 77.4% while the remaining 22.6% is influenced by other variables which were not researched and explained in this research.